Efficacy of kangaroo mother care combined with neonatal phototherapy in newborns with non-pathological jaundice: A meta-analysis - Chen, Ping; Chen, Meiling; Fu, Rongrong; He, Wei; He, Yujing; Shentu, Haojie; Gu, Lihu (Frontiers in Pediatrics, 2023)
Background: The kangaroo-mother care method (KMC) is a skin-to-skin contact-centered care approach with numerous benefits for neonates, but its impact on the treatment of jaundiced neonates is unknown. This study aimed to investigate the efficacy of KMC combined with neonatal phototherapy (NNPT) in treating neonates with non-pathological jaundice. Methods: Relevant articles were searched in PubMed, Embase, Web of Science, and Cochrane Library databases from database establishment to April 2022. The outcomes included, without limitation, serum bilirubin levels, and duration of phototherapy. Results: This meta-analysis included five studies (4 randomized controlled trials and 1 observational study) involving four hundred eighty-two neonates with non-pathological jaundice. The results showed that the group receiving KMC combined with NNPT had lower serum bilirubin at 72 h after intervention (weighted mean difference (WMD) = -1.51, p = 0.03), shorter duration of phototherapy (standard mean difference (SMD) = -1.45, p < 0.001) and shorter duration of hospitalization (SMD = -1.32, p = 0.002) compared to NNPT group. There was no difference in peak bilirubin in both groups of neonates (WMD = -0.12, p = 0.62). Conclusions: KMC combined with NNPT helped to treat non-pathological jaundice in newborns compared to NNPT alone.